Education and Counseling on Adolescent Reproductive Health in High School: Edukasi dan Penyuluhan Tentang Kesehatan Reproduksi Remaja di Sekolah Menengah Atas - Dadang Muhammad Hasyim; Elvina Triana Putri; Desty Endrawati Subroto; Sulaeman; Habibi (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
Reproductive health is an important aspect that adolescents need to understand to maintain their physical and mental well-being. This community service program aims to provide education and counseling about reproductive health to students of IT As-Syakur High School, targeting students aged 16-18 years. The methods used include face-to-face counseling, interactive discussions, simulations, and utilizing digital platforms for self-study. The material presented covers reproductive anatomy, the risks of sexually transmitted diseases (STDs), early pregnancy, contraception, and psychosocial aspects related to relationships and decision-making. The implementation results showed a significant increase in students' understanding after the counseling, with an average improvement from 60% to 85% in the post-test. A total of 90% of students understood reproductive anatomy, while 85% understood the risks of STDs, and 80% mastered the material on contraception. The use of digital media by 65% of students for self-study also demonstrated the program's effectiveness. This program successfully addressed the stigma among students regarding reproductive health and encouraged their active involvement in learning. This success provides a strong foundation for implementing similar programs in the future with a broader scope, involving parents and teachers, and supporting the sustainability of the program through a technology-based approach. Abstrak Kesehatan reproduksi merupakan aspek penting yang perlu dipahami oleh remaja untuk menjaga kesehatan fisik dan mental mereka. Program pengabdian ini bertujuan untuk memberikan edukasi dan penyuluhan tentang kesehatan reproduksi kepada siswa SMA IT As-Syakur, dengan target siswa berusia 16-18 tahun. Metode yang digunakan melibatkan penyuluhan tatap muka, diskusi interaktif, simulasi, dan pemanfaatan platform digital untuk belajar mandiri. Materi yang disampaikan mencakup anatomi reproduksi, risiko penyakit menular seksual (PMS), kehamilan dini, kontrasepsi, serta aspek psikososial terkait hubungan dan pengambilan keputusan. Hasil pelaksanaan menunjukkan adanya peningkatan signifikan dalam pemahaman siswa setelah penyuluhan, dengan peningkatan rata-rata dari 60% menjadi 85% pada post-test. Sebanyak 90% siswa memahami anatomi reproduksi, sementara 85% memahami risiko PMS, dan 80% menguasai materi tentang kontrasepsi. Penggunaan media digital oleh 65% siswa untuk belajar mandiri juga menunjukkan efektivitas program. Program ini berhasil mengatasi stigma yang ada di kalangan siswa mengenai kesehatan reproduksi dan mendorong keterlibatan aktif mereka dalam pembelajaran. Keberhasilan ini memberikan dasar kuat untuk penerapan program serupa di masa depan dengan cakupan yang lebih luas, melibatkan orang tua dan guru, serta mendukung keberlanjutan program melalui pendekatan berbasis teknologi.